The Effect of Recruitment Process and Loyalty on the Work Commitment of Indonesian National Army (TNI) Personnel on Service at the Jayakarta Regional Military Command - Wiguna, Budi Satria; Hermina, Nurul (Universitas Proklamasi 45, 2023)
Military District Command (Kodam) / Kodam Jaya is a military district based in the Special Capital City Region (DKI) Jakarta with its headquarters in East Jakarta City. Kodam Jaya is one of the military districts that accepts prospective personnel who is already a member of the Indonesian National Army (TNI) in the DKI Jakarta area and its surroundings. The personnel of Kodam Jaya have high dedication by showing good performance and are able to coordinate between personnel. However, the work performance shown by Kodam Jaya personnel is less committed to work, as evidenced by the reluctance to be transferred to the other sub-units that are still within the Jaya Regional Military Command. Given these problems, this research is to find out the results of the analysis of the influence of the recruitment process and personnel loyalty in determining the work commitment of personnel on duty at Kodam Jaya. This study used a descriptive-quantitative method, with 133 respondents who were known to be from the Kodam Jaya personnel. By using the Slovin formula in sampling, the study uses regression analysis to find out the relationship between variables. The results of this research, it was found that the recruitment process and loyalty can determine the work commitment of Kodam Jaya personnel with high influence. However, the recruitment process has a very low influence on the work commitment of Kodam Jaya personnel.